Direito, norma e biopoder em Michel Foucault - Ricardo Manoel de Oliveira Morais (2015)
The present research attempt to exam, in Michel Foucaults thought, three different articulations of the Law, in order to associate them with the concepts of discipline, biopolitics, Power and truth and the way that these elements were decisive in inventions and biopower strategies. Thus, it will evidence that the law for the author should be understood not as restricted to law or legal theories, but as a tangle of strategies, speeches and relationships, permeated by power, beyond the repressive legalism. Considering that the right has different joints at the thought of the philosopher, the research will evidence: 1) the right as judicial practices arising from the power relations interspersed with elements of truth; 2) the right as a sovereign global instance that mask the disciplinary strategies of power, which can be translated into law and norm; 3) the right as local forms of domination and rules in the global biopolitical strategies. Considering that the juridical field is permeated by relations of domination, the analysis will articulate the theme of the knowledge of the truth regimes, placing the right as a field permeates by the power-truth, as what touches the disciplinary power and the sovereign theories and as a set of techniques in biopolitical governamentality.